2021
DOI: 10.3390/ijerph18063275
|View full text |Cite
|
Sign up to set email alerts
|

Can Environmentally Sustainable Development and Green Innovation of Hotels Trigger the Formation of a Positive Brand and Price Premium?

Abstract: This study develops a theoretical framework to describe brand images and customer behaviors in relation to the eco-friendly activities of hotels. These eco-friendly activities were divided into environmentally sustainable development and green innovation. In this study, a survey was conducted on customers who had used a hotel in the past year, and a total of 329 valid samples were obtained. The empirical analysis was conducted using SPSS 22.0 and AMOS 22.0. The empirical analysis results showed that hotels’ ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Products from organic production are referred to as biological, biodynamic, or organic products [46,47], and organic products are increasingly being chosen by people who care about their health and also by those who care about the environment. Under the regulation of the European Parliament and the Council of the EU, an organic product is a product that comes from organic production.…”
Section: Characteristics Of the Market Of Eco-friendly Productsmentioning
confidence: 99%
“…Products from organic production are referred to as biological, biodynamic, or organic products [46,47], and organic products are increasingly being chosen by people who care about their health and also by those who care about the environment. Under the regulation of the European Parliament and the Council of the EU, an organic product is a product that comes from organic production.…”
Section: Characteristics Of the Market Of Eco-friendly Productsmentioning
confidence: 99%
“…For brands that operate positioning focused on environmental sustainability, strategic management that presents their perspectives and concerns for the environment through the signs adopted in their speech is essentially important (Østergaard et al, 2015). Since sustainable activities positively in uence its performance and provide signi cant insights, the understanding of these activities is usually perceived by the symbolism imbued with brand signs, since to understand and communicate complex meanings about the value, status and morality of the company and the Consumers of the commodity make use of the perceived use of identi able means applied by the company (Yu et al, 2021).…”
Section: "(…)mentioning
confidence: 99%
“…Physical, chemical, and biological processes are used to manage the reduction of unpleasant and hazardous characteristics of large amounts of waste generated [3]. As such, the amount of water consumption and wastewater generation in hotels is at a level that cannot be ignored and is much likely to continue to increase in the future [6,13]. Furthermore, it has the potential to pose a very high risk to human life by causing environmental problems such as global warming, fine dust, carbon emissions, and water pollution [14].…”
Section: Water Conservation Management and Waste Reduction Measuresmentioning
confidence: 99%
“…Emphasis on the importance of ecofriendliness in the hospitality industry and its sustainability is due to strong consumer demands for eco-friendly products and services [4,5]. This change in consumers' perception of the environment is because they witness the damage posed by environmental degradation, and they continue to demand measures to minimize pollution and take environmentally responsible actions [6]. A study by TripAdvisor found that travelers are concerned about environmental issues when making hotel decisions [5,7].…”
Section: Introductionmentioning
confidence: 99%